From wages to widgets: how minimum wage hikes fuel automation - Shahab Sharfaei; Jakkrit Thavorn (Humanities & Social Sciences Communications)
Abstract This study considers the relationship between the recent technological advancements in robotics and three key economic factors which arguably define labour market well-being: wages, productivity, and labour share. Given these advancements, many forecasts have been made regarding the repercussions of technological adoption for the labour market. However, we rely on empirical evidence to examine these phenomena and project the future trajectory. By developing a theoretical model and using data on robot adoption from six European economies that implemented minimum wage in the 21st century, this study analyses the effects of minimum wage policies on robot adoption and, in turn, the impact of robot adoption on productivity and labour share. Our findings suggest that the implementation of minimum wage policies is associated with an increase in robot installations, which, subsequently results in higher productivity and a greater labour share of income.